Equating Principles in Assessment: A Literature Review in the Context of Education and Assessment - Fitrah, Muh.; Ilyas, Ilyas; Akbarini, Nur Rahmi; Oscar, Oscar; Istiyono, Edi; Widihastuti, Widihastuti (IJECA (International Journal of Education and Curriculum Application), 2023)
This literature review explores the fundamental concepts and methods related to equating principles in the context of educational assessment. Equating, as a complex statistical technique, plays an increasingly crucial role in ensuring fairness and accuracy in test-based assessments. The literature review methodology begins with the identification of key themes regarding equating principles in education and assessment. It utilizes keywords and scholarly databases to search for relevant sources, selecting those that are up-to-date and possess robust methodologies. The result is a deeper understanding of the concept of equating in the context of educational assessment. The study highlights the significant relevance of equating in education, where test results are often used for critical decision-making. Extensive discussions on the practical implications of implementing equating in educational policy and assessment, as well as its impact on students, teachers, and educational institutions, are presented. In conclusion, a critical understanding of equating is essential to ensure fair, consistent, and meaningful assessments in an ever-evolving educational landscape.